2017
DOI: 10.1103/physreva.95.022503
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of quantum many-body chaos in the protactinium atom

Abstract: Energy level spectrum of protactinium atom (Pa, Z = 91) is simulated with a CI calculation. Levels belonging to the separate manifolds of a given total angular momentum and parity J π exhibit distinct properties of many-body quantum chaos. Moreover, an extremely strong enhancement of small perturbations takes place. As an example, effective three-electron interaction is investigated and found to play a significant role in the system. Chaotic properties of the eigenstates allow one to develop a statistical theo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Sufficiently complex elements have spectra with chaotic properties [120][121][122]. The analysis techniques necessary for understanding these spectra bridge many disciplines, ranging from collisions in ultracold atoms [123] to dielectronic recombination (a process where an electron is captured by an atom and this capture is accompanied by excitation of a initially bound electron) [124] and the spectra of nuclei.…”
Section: Ideas For Future Experimentsmentioning
confidence: 99%
“…Sufficiently complex elements have spectra with chaotic properties [120][121][122]. The analysis techniques necessary for understanding these spectra bridge many disciplines, ranging from collisions in ultracold atoms [123] to dielectronic recombination (a process where an electron is captured by an atom and this capture is accompanied by excitation of a initially bound electron) [124] and the spectra of nuclei.…”
Section: Ideas For Future Experimentsmentioning
confidence: 99%
“…For instance, the five valence electrons of its free atom may spread in numerous ways on the valence 5f, 6d, 7s and 7p shells, which generates a quantum chaos of states even well before ionization. [2][3][4] In solution, protactinium chemistry is expected to be dominated by its +V oxidation state (formally free of valence electron), with potential occurrence under specific reducing conditions of the unstable +IV one (displaying one unpaired 5f electron in the ground state). 5 Therefore, the aqueous chemistry of protactinium could well have been dominated by easily identifiable and computable species.…”
Section: Introductionmentioning
confidence: 99%
“…Based on theoretical predictions indicating a potentially chaotic behavior of the atomic structure [243] these experimental levels were then investigated. Using statistical methods and simulation studies indicated that from the neighbor spacing and the level density for this atom the level distribution does no longer match classically integrable systems but rather shows an intrinsically fully chaotic behavior already at energies well below the first ionization potential.…”
Section: Quantum Chaos In the Atomic Spectrum Of Protactiniummentioning
confidence: 99%